2006
DOI: 10.1161/circulationaha.105.586727
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Magnetic Resonance Imaging–Guided Endovascular Recanalization of Chronic Total Arterial Occlusion in a Swine Model

Abstract: Background-Endovascular recanalization (guidewire traversal) of peripheral artery chronic total occlusion (CTO) can be challenging. X-ray angiography resolves CTO poorly. Virtually "blind" device advancement during x-ray-guided interventions can lead to procedure failure, perforation, and hemorrhage. Alternatively, MRI may delineate the artery within the occluded segment to enhance procedural safety and success. We hypothesized that real-time MRI (rtMRI)-guided CTO recanalization can be accomplished in an anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 45 publications
0
52
0
Order By: Relevance
“…If this could be combined with technologies that allow precise wire steering and effective wire advancement, the triad of capabilities required to elevate the success of crossing CTOs (coronary and peripheral) to the 95% to 98% success rate now achieved for subtotal stenosis would be in place. In this issue of Circulation, Raval et al 6 from the cardiovascular branch of the National Heart, Lung, and Blood Institute share a provocative preliminary animal study suggesting that magnetic resonance imaging (MRI) fluoroscopy, coupled with catheters and guidewires equipped to serve as active antennas within the MRI system, may be able to fulfill that goal.…”
Section: Article P 1101mentioning
confidence: 99%
See 2 more Smart Citations
“…If this could be combined with technologies that allow precise wire steering and effective wire advancement, the triad of capabilities required to elevate the success of crossing CTOs (coronary and peripheral) to the 95% to 98% success rate now achieved for subtotal stenosis would be in place. In this issue of Circulation, Raval et al 6 from the cardiovascular branch of the National Heart, Lung, and Blood Institute share a provocative preliminary animal study suggesting that magnetic resonance imaging (MRI) fluoroscopy, coupled with catheters and guidewires equipped to serve as active antennas within the MRI system, may be able to fulfill that goal.…”
Section: Article P 1101mentioning
confidence: 99%
“…Despite these considerable challenges, Raval et al 6 have demonstrated feasibility of using MRI guidance to recanalize carotid artery CTO in a swine model. Several technical developments were required: Nonmagnetic materials (MP35N, nitinol) were used to build custom guidewires, loopless and microcoil active antennas were created on the guidewires and catheters to allow real-time detection of these devices, and the microcoils and their associated circuitry were detuned and decoupled to prevent device heating during real-time MRI.…”
Section: Article P 1101mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern scanners designed for the interventional environment can provide real-time images of acceptable quality in excess of 10 frames per second. As a result, real-time MRI (rtMRI) is becoming an attractive method for many minimally invasive cardiac interventions (Kuehne et al, 2003, Raval et al, 2006, Henk et al, 2005, McVeigh et al, 2006, Horvath et al, 2007. However the confined physical space of MRI scanner challenges medical intervention, even the magnets with open architecture provide only a limited working space, at the expense of image quality.…”
Section: Introductionmentioning
confidence: 99%
“…More promising future technologies might include forward-looking intravascular ultrasound [7,8] or perhaps better, conducting the entire recanalization procedure under real-time MRI guidance [9] to assure wholly intraluminal guidewire traversal.…”
mentioning
confidence: 99%